Produção de mudas de enterolobium contortisiliquum (vell.) morong em dois níveis de luminosidade e substratos - Ramos, Paulo Henrique Leite (2018)
The objective of this study was to evaluate the production of Enterolobium contortisiliquum (Vell.) Morong (monkfish) seedlings at two levels of luminosity and substrates. It was used completely randomized design in factorial 4 x 2 (four substrates and two environments) with four replications of 16 plants in each plot. The substrates were: soil (S1); soil + cattle manure 2:1 v/v (S2); soil + cattle manure 3:1 v/v (S3) and soil + NPK (5-25-15) + Zn (S4). Environments were in full sun and 50% light. The evaluated characteristics were: leaf number (NF); stem diameter (DC); shoot length (CPA); roots length (CR); dry matter of shoot (MSA); dry matter of roots (MSR); and index quality of Dickson (IQD). E.contortisiliquum seedlings with higher quality can be produced in full sun in substrates with soil and cattle manure.